No N-raising out of NPs in Spanish: ellipsis as a diagnostic of head movement - Lipták, Anikó (2014)
In this paper, we present a novel test for diagnosing head movement across languages, based on the availability of X-stranding XP-ellipsis. As we argue, X-stranding XP-ellipsis phenomena should exist in languages where XP-ellipsis and X-movement out of XP are both available (as is the case in V-stranding VP-ellipsis in Hebrew or Portuguese, see Goldberg 2005 and references cited there). This has the effect that if a language has XP-ellipsis but lacks X-stranding XP-ellipsis, X-movement out of XP must be lacking in the language. We show the application of this test in the nominal domain, for the particular case of Spanish, one of the languages for which N-raising out of the NP has been proposed in the literature (Bosque and Picallo 1996). Spanish indeed has productive instances of NP-ellipsis, but lacks N-stranding NP-ellipsis. Carefully ruling out other reasons for the lack of N-standing NP-ellipsis, the paper shows that it can only be due to the lack of N-movement out of NP.